Adjacent cervical ganglioneuromas - Ahmed Abdelghaffar Helal; Refat Badawy; Mohamed Mahfouz; Tharwat Hussien (Elsevier, 2018)
Ganglioneuroma is a rare benign neurogenic tumor. It presents as a solitary, painless and slow-growing mass. Dumbbell ganglioneuroma in the cervical region is extremely rare. The reported incidence of ganglioneuroma is one per million populations. We describe a new case of dumbbell cervical ganglioneuroma and review the literature for relevant data.